2023
DOI: 10.30659/odj.10.2.314-325
|View full text |Cite
|
Sign up to set email alerts
|

The role of Treponema denticola in the periodontitis alveolar bone damage: Systematic review

Erik Idrus,
Willy Hartanto,
Widya Lestari
et al.

Abstract: Background: Periodontitis is a chronic inflammation condition of the periodontal tissue, which causes irreversible, progressive deterioration of the tooth-supporting tissue, leading to tooth loss. One of the main bacteria in the pathogenesis of periodontitis is Treponema denticola. Its involvement in periodontitis includes producing and releasing various virulence factors that further modulate inflammation and ignite alveolar bone destruction. Objective: To examine Treponema denticola's role in the mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated that these factors induce pro-inflammatory cytokines like IL-1β, IL-6, and TNF-α, leading to increased osteoclastogenesis through TLR2, MyD88, and Sp1 pathways. This inflammatory response results in increased RANKL expression and decreased OPG expression, promoting bone resorption and periodontal tissue damage ( 33 ). Prevotella species produce a variety of virulence factors, including proteases, lipopolysaccharides (LPS), hyaluronidase, and collagenase, which degrade host structural proteins such as collagen and elastin, initiating a robust inflammatory response ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that these factors induce pro-inflammatory cytokines like IL-1β, IL-6, and TNF-α, leading to increased osteoclastogenesis through TLR2, MyD88, and Sp1 pathways. This inflammatory response results in increased RANKL expression and decreased OPG expression, promoting bone resorption and periodontal tissue damage ( 33 ). Prevotella species produce a variety of virulence factors, including proteases, lipopolysaccharides (LPS), hyaluronidase, and collagenase, which degrade host structural proteins such as collagen and elastin, initiating a robust inflammatory response ( 34 ).…”
Section: Discussionmentioning
confidence: 99%